Karakteristik Pasang Surut Air Laut di Peairan Belawan Menggunakan Metode Admiralty - Teuku Rahmat Syahputra; Endah Anisa Rahma (Universitas Teuku Umar, 2023)
The purpose of this study is to understand the tidal characteristics using the Admiralty method, namely to determine the tidal harmonic constants and types of tides based on the forrmzahl value in Belawan waters. This research was conducted from March 1 to 29, 2022. The information was obtained from the Meteorology, Climatology and Geophysics Agency (BMKG) at the Belawan Maritime Station in Medan. Information analysis using the Admiralty method. The results showed that the value of the harmonic constant was 28.745. The results of these calculations belong to the category of single daily tidal type. While the evaluation of the height of the water level, the average water level at the time of the full moon (MHWL) is 77.2 cm, the average (MLWL) is 44.2 cm. From the results of this study, it can be determined that Belawan waters have a single daily tidal type.